2021
DOI: 10.3390/diagnostics11122177
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Involvement in IgG4-Related Disease: Case Report and Review of the Literature

Abstract: Diagnostic work-up of IgG4-related disease (IgG4-RD) pleural involvement is a complex task, as there is a broad spectrum of differential diagnoses to consider. We report the case of a patient presenting with relapsing pleural effusion, discussing the main challenges for achievement of a definite diagnosis. A 63-year-old man was admitted for pleural effusion prevalent on the ride side, initially labeled as idiopathic non-specific pleuritis, based on tissue evaluation after a medical thoracoscopy. He was started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
5
2
2
Order By: Relevance
“…IgG4-related pleural thoracoscopic findings varied from normal 17,19,26 to abnormal, which were expressed as numerous small, white, and dense granular lesions and reddish, hyperemia, and blister-like nodules. 9,10,15,21,22,27 This case showed a reddish, thickened pleura, which differs from the findings of most previous reports. Accumulation of pleural findings may provide new information for the diagnosis of IgG4-RD.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…IgG4-related pleural thoracoscopic findings varied from normal 17,19,26 to abnormal, which were expressed as numerous small, white, and dense granular lesions and reddish, hyperemia, and blister-like nodules. 9,10,15,21,22,27 This case showed a reddish, thickened pleura, which differs from the findings of most previous reports. Accumulation of pleural findings may provide new information for the diagnosis of IgG4-RD.…”
Section: Discussioncontrasting
confidence: 99%
“…The risk of postoperative chylothorax should be carefully considered, assuming disruption to the lymphatic pathway. IgG4‐related pleural thoracoscopic findings varied from normal 17,19,26 to abnormal, which were expressed as numerous small, white, and dense granular lesions and reddish, hyperemia, and blister‐like nodules 9,10,15,21,22,27 . This case showed a reddish, thickened pleura, which differs from the findings of most previous reports.…”
Section: Discussioncontrasting
confidence: 64%
“…Yang and colleagues also reported that serum IgG4 level was associated with the number of affected organs ( 40 ). However, it is important to be aware that elevated serum IgG4 levels can also be present in a range of other conditions, including healthy individuals, malignant neoplasms, infectious diseases, and other inflammatory conditions ( 8 ). Therefore, relying solely on serum IgG4 levels is insufficient for diagnosing or ruling out IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, relying solely on serum IgG4 levels is insufficient for diagnosing or ruling out IgG4-RD. IgG4 antibodies may serve as markers for immune-mediated processes as part of more complex inflammatory diseases ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this disease, the PF is an exudate with a predominance of lymphocytes, plasma cells and high concentrations of IgG4. Pleural biopsy shows a fibrosing pleurisy with lymphoplasmacytic inflammation and IgG4-positive plasma cells [104].…”
Section: Pancreatic Diseasesmentioning
confidence: 99%